MODEL SISTEM MANAJEMEN RESIKO PERBANKAN SYARIAH ATAS TRANSAKSI USAHA MASYARAKAT - Rizki Ramadiyah (MENARA RIAU, 2014)
Risk management is a relatively new scientific discipline in the management of the company. Finance and banking industry began to pay great attention to risk management, especially after the events that led to the collapse of this industry since last few decades . Meanwhile, Islamic banking and finance industry requires the expertise along with the rapid development and the global environment continues to move . The risk of Islamic banks appears as in conventional banks minus interest . But unique is that the risks in Islamic banks related to the structure of assets and liabilities that exist in Islamic banks . In the asset side , Islamic banks filled by berbada financial instruments with conventional banks . He did not know the interest despite the instrument that gives a definite advantage . While the liabilitasya side , Islamic banks charged by financial instruments that require customers to share the results with customers considering only invest his wealth in the form of money . Contracts made in mobilizing both sides provide important implications for the risk profile faced by Islamic banks . Islamic Bank will face six types of risk ( IFSB - version of Islamic Financial Services Board - ) , namely : Credit Risk ( credit risk ) , Equity Investment Risk ( risk of equity investment ) , Market Risk ( market risk ) , Liquidity Risk ( liquidity risk ) , rate of Return risk ( risk rate of return ) , operational Risk ( operational risk ) . Meanwhile , according to Bank Indonesia Regulation No. 5/8 of 2003 on the Application of Risk Management for Banks , banks will face at least eight types of risk , namely : 1 ) Credit Risk ; 2 ) Market Risk; 3) Liquidity Risk ; 4 ) Operational Risk ; 5 ) Legal Risk ; 6 ) Reputation Risk ; 7 ) Strategic Risk ; and 8 ) Risk Compliance . Four first risk is the risk that a financial institution owned by each of the different levels of complexity of bank operations . Each bank shall manage those risks in accordance with the needs of the concerned bank . While the last four risks associated with the complexity of the bank in which the bank will face the risk of a more diverse and difficult